Factors Affecting Artificial Insemination Pregnancy Outcome - Wang X; Zhang Y; Sun HL; Wang LT; Li XF; Wang F; Wang YL; Li QC (International Journal of General Medicine, 2021)
Xue Wang,* Yue Zhang,* Hong-Liang Sun, Li-Ting Wang, Xue-Feng Li, Fei Wang, Yan-Lin Wang, Qing-Chun Li Department of Reproductive Medicine, Binzhou Medical University Hospital, Binzhou, 256603, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qing-Chun Li; Yan-Lin WangDepartment of Reproductive Medicine, Binzhou Medical University Hospital, No. 661 Huanghe 2nd Road, Binzhou, 256603, People’s Republic of ChinaTel +86 543 325 8715; +86 543 325 8713Fax +86 543 325 7792Email qingchunli_doc@163.com; docylwang2003@163.comObjective: The aim of the present study was to explore related clinical pregnancy outcome factors in intrauterine insemination (IUI).Materials and Methods: The clinical data of 3984 IUI cycles in 1862 couples experiencing infertility who attended the Reproductive Center of Binzhou Medical University Hospital between July 2006 and July 2017 were retrospectively analyzed. Female and male patient age, endometrial thickness (EMT), the post-wash total motile sperm count (PTMC), artificial insemination timing, insemination frequency, and ovarian stimulation protocols were compared between the study’s pregnant group and non-pregnant group in order to explore any correlation.Results: There were statistically significant differences in female and male age, EMT, artificial insemination timing, insemination frequency, and ovarian stimulation protocols between the two groups (p < 0.05). The clinical pregnancy rate was significantly higher in ovarian stimulation cycles than in natural cycles (21.2% and 11.6%, respectively; p < 0.01), the clinical pregnancy rate was significantly higher in double IUI than in single IUI (17.8% and 12.1%, respectively; p < 0.01), and EMT was significantly greater in the pregnant group than in the control group (p < 0.05). However, the differences in clinical pregnancy rates among the PTMC groups were not statistically significant (14.8%, 14.4%, 17.3%, and 17.3%, respectively; p > 0.05).Conclusion: The results of the present study demonstrate that the clinical IUI pregnancy rate is correlated with the factors of female age, male age, EMT, artificial insemination timing, insemination frequency, and ovarian stimulation protocols; the ovarian stimulation protocol can noticeably improve the patient pregnancy outcome. Furthermore, compared with single IUI, double IUI can significantly increase the clinical pregnancy rate.Keywords: intrauterine insemination, clinical pregnancy rate, post-wash total motile sperm count, ovarian stimulation cycle, timing of intrauterine insemination